Role of the intrinsic subtalar ligaments in subtalar instability and consequences for clinical practice - Michels, Frederick; Vereecke, Evie; Matricali, Giovanni (Frontiers in Bioengineering and Biotechnology, 2023)
Subtalar instability (STI) is a disabling complication after an acute lateral ankle sprain and remains a challenging problem. The pathophysiology is difficult to understand. Especially the relative contribution of the intrinsic subtalar ligaments in the stability of the subtalar joint is still controversial. Diagnosis is difficult because of the overlapping clinical signs with talocrural instability and the absence of a reliable diagnostic reference test. This often results in misdiagnosis and inappropriate treatment. Recent research offers new insights in the pathophysiology of subtalar instability and the importance of the intrinsic subtalar ligaments. Recent publications clarify the local anatomical and biomechanical characteristics of the subtalar ligaments. The cervical ligament and interosseous talocalcaneal ligament seem to play an important function in the normal kinematics and stability of the subtalar joint. In addition to the calcaneofibular ligament (CFL), these ligaments seem to have an important role in the pathomechanics of subtalar instability (STI). These new insights have an impact on the approach to STI in clinical practice. Diagnosis of STI can be performed be performed by a step-by-step approach to raise the suspicion to STI. This approach consists of clinical signs, abnormalities of the subtalar ligaments on MRI and intraoperative evaluation. Surgical treatment should address all the aspects of the instability and focus on a restoration of the normal anatomical and biomechanical properties. Besides a low threshold to reconstruct the CFL, a reconstruction of the subtalar ligaments should be considered in complex cases of instability. The purpose of this review is to provide a comprehensive update of the current literature focused on the contribution of the different ligaments in the stability of the subtalar joint. This review aims to introduce the more recent findings in the earlier hypotheses on normal kinesiology, pathophysiology and relation with talocrural instability. The consequences of this improved understanding of pathophysiology on patient identification, treatment and future research are described.